2019
DOI: 10.1016/j.yhbeh.2019.104580
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between male social status, ejaculate and circulating testosterone concentration and female yolk androgen transfer in red junglefowl (Gallus gallus)

Abstract: Several studies show that avian females prefer males based on their secondary sexual ornaments and dominance status. We tested in red junglefowl (Gallus gallus) how comb size affected the result of fighting and how the dominance status related to testosterone concentrations in their circulation and ejaculates. We subsequently tested how social status was related to female reproductive investment, including yolk hormone transfer. We found that after a fight 1) winners increased plasma T and decreased ejaculates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 78 publications
(85 reference statements)
0
7
0
2
Order By: Relevance
“…Firstly, the resulting deposition could have been masked by a mechanism in which hens further differentiated their hormone allocation according to offspring sex. Such a mechanism is present in the ancestral species of laying hens, the red junglefowl (Lelono et al, 2019), in laying hens themselves (Müller et al, 2002), house sparrows (Badyaev et al, 2005) and has also been demonstrated in other species e.g. zebra finches (Gilbert et al, 2005; Rutstein et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Firstly, the resulting deposition could have been masked by a mechanism in which hens further differentiated their hormone allocation according to offspring sex. Such a mechanism is present in the ancestral species of laying hens, the red junglefowl (Lelono et al, 2019), in laying hens themselves (Müller et al, 2002), house sparrows (Badyaev et al, 2005) and has also been demonstrated in other species e.g. zebra finches (Gilbert et al, 2005; Rutstein et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…One possibility that may have confounded this lack of effect is that there was a mechanism in action, as mentioned above, in which hens differentially allocated hormones to eggs in an offspring sex-dependent way. Fowl are capable of offspring-sex-dependent hormone deposition (Lelono et al, 2019; Müller et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al ., 2019 b ), a father has little information about emerging offspring phenotype until shortly before its hatching or birth, when embryos' movement and vocalisations are detectable from the outside (Vergne & Mathevon, 2008 ; Noguera & Velando, 2019 ). Fathers may have a direct effect on hormone allocation to embryos: there is evidence that seminal hormones can influence offspring phenotype (Lelono et al ., 2019 ), while fathers in species with external development may have direct opportunities to expose embryos to various substances of paternal origin (Keller‐Costa et al ., 2015 ). However, fathers have no way of estimating emerging offspring phenotype, and hence whether this differs from their own optimum, until the offspring is born or hatches.…”
Section: Adaptive Plasticity In Response To Maternal Hormone Signalsmentioning
confidence: 99%
“…We argue that understanding the link between maternal hormone allocation and offspring phenotype requires understanding which family member strategies have evolved under intrafamilial conflict, which in turn depends on the ecological and social context. embryonic development directly by exposing offspring to their own hormones, for example through semen in species with internal fertilisation (Lelono, Riedstra & Groothuis, 2019) or through urine in species with external fertilisation (Keller-Costa, Canàrio & Hubbard, 2015). Offspring and fathers, then, are limited in what maternal hormone signals they receive, but not necessarily in what they do with those signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation